Studies on human eRF3-PABP interaction reveal the influence of eRF3a N-terminal glycin repeat on eRF3-PABP binding affinity and the lower affinity of eRF3a 12-GGC allele involved in cancer susceptibility. Issue 3 (3rd March 2016) - Jerbi, Soumaya; Jolles, Béatrice; Bouceba, Tahar; Jean-Jean, Olivier
ABSTRACT: The eukaryotic release factor 3 (eRF3) has been involved in the control of mRNA degradation through its association with the cytoplasmic Poly(A) Binding Protein, PABP. In mammals, eRF3 N-terminal domain contains two overlapping PAM2 motifs which specifically recognize the MLLE domain of PABP. In humans, eRF3a/GSPT1 gene contains a stable GGC repeat encoding a repeat of glycine residues in eRF3a N-terminus. There are five known eRF3a/GSPT1 alleles in the human population, encoding 7, 9, 10, 11 and 12 glycines. Several studies have reported that the presence of eRF3a 12-GGC allele is correlated with an increased risk of cancer development. Using surface plasmon resonance, we have studied the interaction of the various allelic forms of eRF3a with PABP alone or poly(A)-bound PABP. We found that the N-terminal glycine repeat of eRF3a influences eRF3a-PABP interaction and that eRF3a 12-GGC allele has a decreased binding affinity for PABP. Our comparative analysis on eRF3a alleles suggests that the presence of eRF3a 12-GGC allele could modify the coupling between translation termination and mRNA deadenylation.